Work experience and school workers’ health evaluated by salutogenic health indicators - Jurgita ANDRUŠKIENĖ; Deimantė KIRVELIENĖ; Arvydas MARTINKĖNAS; Ingemar ANDERSSON; Göran EJLERTSSON (Acta Medica Lituanica, 2011)
Background. The aim of the study was to establish relations between work experience and health, evaluated by salutogenic health indicators, among school workers. Materials and methods. Teachers (n = 180) and other school workers (n = 154) from randomly selected Panevėžys district schools were questioned using instruments developed by scientists of the Kristianstad University: the Work Experience Measurement Scale (WEMS) and Salutogenic Health Indicator Scale (SHIS). The questionnaire of personal data contained questions about sociodemographic and work-related characteristics. The differences among the mean values were tested by the independent samples t-test and one-way ANOVA. The Cronbach’s alpha coefficient was used to check the internal consistency. The significance level was accepted at p = 0.05. Results. In the teachers’ group, 86.7% were females (75.3% among others), 20.4% were older than 55 years (30.7% in other goups), 18.9% held an executive position (8.5% among others). Teachers, as compared with other school workers, scored higher the domain of internal work experience, (76.9 vs. 62.8, respectively), while other school workers gave higher standardized scores for the time experience domain (71.9 vs. 63.7, p < 0.001 respectively). The SHIS scores among teachers varied from 54.7 (worst experience) to 78.0 (best experience), p < 0.001. In the group of other school workers, the SHIS mean scores varied from 51.9 to 80.0, p < 0.001. Conclusions. Teachers more positively evaluated the domain of internal working experience, while other school workers were more satisfied with time experience at the workplace. The established strong correlation between work experience and health, measured by salutogenic health indicators, encouraged the idea to implement workrelated health promotion at school.